Формування врожаю зеленої маси еспарцету залежно від мікродобрив в Степу України - Плескун, Юрій Вікторович; Pleskun, Yurii (ЦНТУ, 2024)
В даній кваліфікаційній роботі вивчено вплив мікродобрив на урожайність еспарцету. Мета досліджень – вивчити оптимальне мікродобриво для посівів еспарцету. Встановлено, що застосування мікродобрив позитивно відображається на онтогенезі еспарцету та сприяє підвищенню його урожайності в умовах Степу України. In this qualification work, the influence of microfertilizers on the productivity of sainfoin was studied. The purpose of the research is to study the optimal level of micronutrient supply to sainfoin. It has been established that the use of microfertilizers has a positive effect on the ontogeny of sainfoin and contributes to an increase in its yield in the Ukrainian Steppe.
Formation of sainfoin green mass yield depending on microfertilisers in the Steppe of Ukraine
Keywords: еспарцет; мікродобрива; врожайність; sainfoin; microfertilisers; yield